CT-GUIDED STEREOTAXY: FIRST 10-YEAR EXPERIENCE - Herman, Miroslav; Dvorak, Petr; Houdek, Michael (Biomedical papers, 2003)
The authors present an overview on CT-guided stereotaxy performed in the last 10 years in the University Hospital Olomouc. During this period a total of 811 stereotactic brain operations were performed. Of these, 710 were done in the field of afunctional and 101 in the field of functional stereotaxy. The majority of procedures were biopsies of intracranial lesions (n = 464), evacuations of intracerebral hematomas with or without drainage and fibrinolysis (n = 147) and thalamotomies in patients with Parkinson's disease (n = 88). With the exception of the two years at the beginning, the number of yearly performed stereotaxies varied between 66-106 (mean, 86.9). Serious complications appeared after three procedures (0.37 %).
Keywords: Stereotaxy / CT / Brain biopsy / Intracerebral hematoma / Fibrinolysis / Parkinson's disease / Compli-cations